DISTRIBUTION OF SKILL REQUIREMENTS FOR INFORMATION TECHNOLOGY GRADUATES IN INDONESIA - Rinartha, Komang; Luh Gede Surya Kartika (Fakultas Dharma Duta UHN IGB Sugriwa Denpasar, 2023)
The objective of this study was to get further insights into the significance of both hard skills and soft skills in securing employment within Indonesia's Information Technology (IT) industry till 2023. To enhance their abilities and effectively vie with their counterparts, IT graduates must possess a clear understanding of the specific talents that organisations require. Universities and other policymakers should utilise this knowledge to develop a plan that aligns the abilities required in the practical world with the skills necessary for graduation. Scraping techniques were employed to retrieve data from three Indonesian job board websites. Data for this study was managed using text processing and statistical techniques. Furthermore, the material underwent cleaning prior to analysis. According to the survey, Web Development, Programmer, and Help Desk Support are the predominant categories of online IT occupations. Out of the twenty highest-ranking occupations, fourteen were exclusively focused on developing software, applications, or programming for mobile or web platforms. Additionally, there was a Network Engineer, a Data Engineer, a Data Analyst, and a System Analyst as jobs that are also widely offered. SQL emerged as the leading computer language. Employers highly value applicants that possess proficiency in SQL as well as another programming language such as Java, C++, or PHP. Collaborative teamwork is consistently the most highly desired ability among employers. Motivated by a strong aptitude for acquiring knowledge and employing analytical thinking. All three of these factors are interconnected with IT projects, which often encompass a diverse array of employment roles.